2022
DOI: 10.1097/md.0000000000030194
|View full text |Cite
|
Sign up to set email alerts
|

A network pharmacology approach to identify the mechanisms and molecular targets of curcumin against Alzheimer disease

Abstract: Background: Alzheimer disease (AD) is a degenerative brain disease, which may lead to severe memory loss and other cognitive disorders. However, few effective drugs are available in the clinic at present. Curcumin, a major ingredient of traditional Chinese medicine, Curcuma Longa, has various pharmacological activities. Therefore, exploring clinical drugs based on the inhibition of AD pathological features is imperative. Methods: First, we utilized the HERB database and Swisstarget Prediction database to get… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…and 150-300 mg/kg oral gavage per day treatment (Fikry et al, 2022;Rajeswari & Sabesan, 2008;Sharma & Nehru, 2018;Zheng et al, 2017). Also, in clinical trials of AD and PD patients, curcumin is reported to be used at doses from 0.08 to 4 g daily by oral administration (Ghodsi et (Maiti et al, 2021;Tello-Franco et al, 2013;Wu et al, 2022). Similar findings were also demonstrated by in vivo studies along with the improvement of memory functions in mice models of AD (Yang et al, 2005;Zheng et al, 2017).…”
Section: Plant-derived Polyphenolsmentioning
confidence: 68%
See 1 more Smart Citation
“…and 150-300 mg/kg oral gavage per day treatment (Fikry et al, 2022;Rajeswari & Sabesan, 2008;Sharma & Nehru, 2018;Zheng et al, 2017). Also, in clinical trials of AD and PD patients, curcumin is reported to be used at doses from 0.08 to 4 g daily by oral administration (Ghodsi et (Maiti et al, 2021;Tello-Franco et al, 2013;Wu et al, 2022). Similar findings were also demonstrated by in vivo studies along with the improvement of memory functions in mice models of AD (Yang et al, 2005;Zheng et al, 2017).…”
Section: Plant-derived Polyphenolsmentioning
confidence: 68%
“…Also, in clinical trials of AD and PD patients, curcumin is reported to be used at doses from 0.08 to 4 g daily by oral administration (Ghodsi et al, 2022; Parikh et al, 2008; Ringman et al, 2012). The inhibitory potential of curcumin upon AChE, Aβ fibril formation and BACE1 activity has been demonstrated by several in silico and in vitro studies (Maiti et al, 2021; Tello‐Franco et al, 2013; Wu et al, 2022). Similar findings were also demonstrated by in vivo studies along with the improvement of memory functions in mice models of AD (Yang et al, 2005; Zheng et al, 2017).…”
Section: Phyto‐compounds and Their Neuroprotective Effects In Ad And ...mentioning
confidence: 94%
“…Curcumin has been widely evaluated with respect to the modulation of endothelial function [ 102 ]. Curcumin also presents a neuroprotective potential in the pathogenesis of Alzheimer’s disease [ 103 , 104 , 105 ]. The many described biological activities of curcumin have been linked to its chemical instability that leads to the rapid autoxidation responsible for its antioxidant behavior.…”
Section: Specific Polyphenolic Compounds Of Interestmentioning
confidence: 99%
“… 10 CUR can more precisely target AD cellular mechanisms and processes that control the production of cytokines. 11 CUR is extracted from the rhizomes of turmeric, which has long been used as a food spice in Southeast Asian countries. 12 The neuroprotection effect of BBR is associated with the inhibition of Akt/ERK1/2 survival/apoptotic signaling pathway/GSK3β/caspase-3 activity and the Jun aminoterminal kinase pathway.…”
Section: Introductionmentioning
confidence: 99%
“…When used separately or together, CUR and BBR significantly improve the management of AD . CUR can more precisely target AD cellular mechanisms and processes that control the production of cytokines . CUR is extracted from the rhizomes of turmeric, which has long been used as a food spice in Southeast Asian countries .…”
Section: Introductionmentioning
confidence: 99%